Pengaruh Iklim terhadap Produksi Kakao di Kabupaten Gunungkidul - Ardiani, Fani; Wirianata, Herry; Noviana, Githa (Politeknik Negeri Lampung, 2022)
Cocoa is one of the commodities as a foreign exchange earner in addition to oil and gas. However, Indonesian cocoa imports have increased from year to year due to low cocoa productivity. Whereas in terms of region, Indonesia has the potential to become a new cocoa power country in the world of cocoa production. This study examines the effect of rainfall, the number of rainy days, and air temperature on cocoa production in the Gunungkidul district. This study uses a quantitative descriptive method. The data used in this study is secondary data in the form of time series data on rainfall, rainy days, air temperature, and cocoa production in 2016-2020 in Gunungkidul Regency. The regression analysis results showed that all observed climatic factors such as rainfall, rainy days, and temperature did not have a significant effect on cocoa production in Gunungkidul Regency. However, the time-series data shows that the highest cocoa production was in October 2017 and November 2018 to January 2019, when rainfall and intensity (rainy days) began to increase. Meanwhile, the air temperature in Gunungkidul Regency for five years is around 24-26°C, which is the optimum temperature for cocoa growth. This study concludes that rainfall, rain intensity (rainy days), and temperature affect fluctuations in cocoa production.